PENDIDIKAN KESEHATAN REPRODUKSI BERBASIS BRAINSTORMING PADA REMAJA PUTRI (BRAINSTORMING BASED REPRODUCTIVE HEALTH EDUCATION IN ADOLESCENT GIRL) - Dianayu, Lia; Aji Permana, Septian (Jurnal Berdaya Mandiri, 2024)
Knowledge about adolescent reproductive health plays an important role where adolescent attitudes are greatly influenced by knowledge about reproductive health. Lack of knowledge about reproductive health can have an impact on risky sexual behavior. It is hoped that education for adolescents can increase knowledge and skills in maintaining adolescent health. Some ways to make teenagers understand more about their health is by getting health information or education, such as counseling about reproductive health, youth counseling, or hanging out with peers. The aim of the activity is to increase knowledge about adolescent reproductive health using brainstorming and counseling methods. This activity was attended by 2nd semester students with a total of 30 participants and was held on June 29th and July 1st 2024 at PGRI University Yogyakarta. The results of this activity show that the brainstorming method is more effective in influencing a person's understanding and health education for late adolescents is carried out as a promotive effort to increase the knowledge and attitudes of adolescents to create overall healthy adolescents. Keywords: Education, Health, Reproduction, Brainstorming, Teenagers